Predictors of recurrent abdominal pain among 9 to 15-year-old urban school-children in Malaysia - Boey, Christopher Chiong Meng; Goh, Khean Lee (Wiley, 2001)
A cross-sectional survey of school-children aged from 9 to 15 y was performed in the city of Petaling Jaya to look for predictors of recurrent abdominal pain. A sample of 1488 children was randomly chosen, of whom 143 (9.6) had recurrent abdominal pain according to Apley's criteria. Conclusion: The results of the study show that recurrent abdominal pain was associated with a number of demographic variables, a tendency to have other complaints and a family history of chronic abdominal complaints.